Analisis Peran Pergerakan Kamera terhadap Surprise (Kejutan) pada Program Komedi “Sketsa” Trans TV - Fina Zahra (Saraswati)
Thesis entitled “Analysis of the Role of Camera Movement Surprise (surprise) on Comedy Program "Sketsa" Trans TV" is a report of research that aims to prove that the camera movement and lens instrumental in visualizing the surprise comedy program "Sketsa" Trans TV. The verification is done by qualitative descriptive method. It describes and analyze qualitative variables in the study based on theories that already exist. An analysis of the data uses the theory of Roy Thompson and Christopher Bowen on the movement in the shot, the start frame, camera movement, and the end frame. Limitations in the research are three types of patterns on the packaging sketch comedy program "Sketsa" Trans TV, which only consists of a single shot, without any editing involved, and there is a movement of the camera or lens movement and prominent in it. The results showed that the camera movement (panning) and the lens movement (zoom out) showed surprise when the end frame is displayed. The result was considered valid and can be accounted for after tested with several existing theories. Keywords: camera movement, lens movement, and surprise (shock).